Plant-Derived Nutraceuticals in Cardiovascular Health: Mechanisms, Clinical Evidence, and Future Perspectives - Ansar Bilyaminu adam1, Musa Yahaya Abubakar, Kabiru Bashir Ahmad; Dalhatu Abubakar (ldealistic Journal of Advanced Research in Progressive Spectrums (IJARPS) eISSN– 2583-6986, 2025)
Cardiovascular diseases (CVDs) continue to be the primary contributors to global morbidity and mortality, necessitating novel strategies for effective prevention and management. Among these, plant-based nutraceuticals have emerged as promising tools due to their natural bioactive compounds with potential cardiovascular benefits. This review delves into the diverse roles of these nutraceuticals, with a particular focus on their mechanisms of action, clinical evidence, and future potential in addressing CVDs. Prominent phytochemicals such as polyphenols, flavonoids, and carotenoids are recognized for their antioxidant, anti-inflammatory, lipid-regulating, and endothelial-supportive properties. Mechanistic insights highlight their ability to mitigate oxidative stress, enhance nitric oxide bioavailability, and suppress pro-inflammatory cytokines. The review also integrates findings from clinical trials, emphasizing the effectiveness and safety of these plant-derived compounds in reducing cardiovascular risk factors like hypertension, dyslipidemia, and atherosclerosis. Looking ahead, the role of nutraceuticals in personalized medicine is explored, supported by advancements in metabolomics and nutrigenomics that enable tailored interventions. Despite their potential, challenges related to standardization, bioavailability, and regulatory compliance are discussed, underscoring the need to bridge gaps between laboratory research and clinical application. This analysis highlights the transformative impact of plant-based nutraceuticals in cardiovascular health and calls for interdisciplinary research to optimize their therapeutic use. By advancing knowledge and application, this review contributes to the global pursuit of sustainable, plant-centered solutions for cardiovascular wellness. Keywords: Cardiovascular diseases (CVDs), Plant-derived nutraceuticals, Phytochemicals, Antioxidant and anti-inflammatory mechanisms, Personalized medicine and nutrigenomics